SIFAT MACHIAVELLIAN DAN ETIKA PROFESI DALAM PERILAKU DISFUNGSIONAL AUDIT - Chasbiandani, Tryas; Satra, Indra; Rizal, Nelyumna (Jurnal Ekonomi : Journal of Economic, 2019)
AbstractThe purpose of this study is to examine the effect of Machiavellian properties in moderating the effect of the relationship of task complexity, locus of control and professional ethics as an antecedent of audit dysfunctional behavior. This research was conducted on auditors working in the East Jakarta and Bekasi regions. This study used a sample of 68 respondents. Data were analyzed using a moderate regression analysis method with the help of the Smart PLS program. The results of this study indicate that locus of control partially influences audit dysfunctional behavior. Machiavellian properties cannot moderate the relationship of task complexity or locus of control to audit dysfunctional behavior, but professional ethics has a significant effect on audit dysfunctional behavior.Â Keywords: Task complexity, locus of control, Machiavellian nature, dysfunctional audit behavior.